Effect of different music tempos on aerobic performance and recovery - Köse, Bereket; Atli, Ahmet (Progress in Nutrition, 2019)
The aim of this study was to determine effect of different music tempos on aerobic performance and recovery period. Thirty-five healthy male students (age=22.63±2.94, body mass=71.40±10.71, height=178.24±9.95) who were studying at Faculty of Sport Sciences voluntarily participated in this study. Participants carried out Bruce treadmill test with 72 hour intervals under three conditions: slow tempo music (100 bpm), fast tempo music (140 bpm) and no music. Anova was applied for statistical analysis. Fast tempo music (18.28±3.01 minute) was determined to improve running time by 4.63% and 3.10% compared to no music (17.47±2.83 min) and slow tempo music (17.73±3.09 min), respectively (p<0.01). Slow and fast tempo music did not have any effect on heart rate (HR) and rate of perceived exertion (RPE) during and after exercise (p>0.05). Lactate accumulation during 15 min recovery was found lower with slow tempo music compared to fast tempo and no music conditions (p<0.05). As a result, it can be concluded that fast tempo music improved running time and performance by creating ergogenic effect while slow tempo music led to fast decreasein heart rate and lactate accumulation during 15 min recovery.